Development of Glassy Bicontinuous Cubic Liquid Crystals for Solid Proton-Conductive Materials - Kobayashi, Tsubasa (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.